Promoting Financial Inclusion through Central Bank Digital Currency: An Evaluation of Payment System Viability in India - Srijanie Banerjee; Manish Sinha (Australasian Accounting, Business and Finance Journal, 2023)
The Reserve Bank of India (RBI) is considering introducing a Central Bank Digital Currency (CBDC). According to studies, India's financial system plays a major role in the execution of the CBDC. India is at the forefront of technological advancements in digital payment methods. The central banks that support CBDC's design concept are susceptible to adaptations to the evolution of economic and financial systems. This study will highlight the potential of CBDC to boost financial inclusion. Quantitative regression analysis is being used to quantify the potential drivers of financial sector efficiency and stability to measure the impact of CBDC implementation on financial inclusion. The central bank should build the CBDC utilizing the Structural Vector Auto-Regression model while considering payment system visibility. The proposed study can help to identify the lags in attaining financial inclusion in India and to design CBDC. The proposed study can also establish the policymakers' role in maximizing benefits to the consumers. The study establishes the potential role of RBI in the smooth functionality of implementing CBDC. The study brings out the trend of the payment system in India that opens up the possibility of positive implementation of CBDC and its welfare to percolate among consumers.
Keywords: Central Bank Digital Currency; Financial Inclusion; Payment System; India